A technological and morphological study of Late Paleolithic ostrich eggshell beads from Shuidonggou, North China. (September 2017) - Wei, Yi; d'Errico, Francesco; Vanhaeren, Marian; Peng, Fei; Chen, Fuyou; Gao, Xing
Abstract: We report the results of a detailed analysis of ostrich eggshell (OES) beads derived mainly from Cultural Layer 2 (CL2) of Locality 2 at the Shuidonggou site (SDG2) in North China, which is dated to ca. 31 ka cal BP. The eggshells belong to the extinct ostrich Struthio anderssoni . Based on microscopic examination, morphometric analysis, and experimental replication, we identify clear differences in morphology, size, technology, and style. Results indicate that the technology of bead making is similar to that used in most Middle and Later Stone Age sites in Africa and recorded ethnographically. Both well-made and poorly-crafted OES beads were produced at SDG2. Drilling experiments conducted in the framework of this study show that hafted stone points were probably used to make the perforations. Only occasionally beads were deliberately polished on inner and outer eggshell surfaces. Beads morphology and technology suggest that distinct types of beads were made by different individual craftspeople. This supports the hypothesis that several human groups visited the Shuidonggou site and used OES beads as an information technology about 31 ka cal BP. Highlights: Ostrich eggshell (OES) beads from Shuidonggou Locality 2 are dated to c. 31 ka cal BP. OES beads are studied by means of experimental replication, microscopic examination and morphometric analysis. Both well-made and poorly-crafted OES beads are found at the site. Distinct types of OES beads were probably made by different craftspeople. Stylistic diversity may reflect the cultural and/or social affiliation of the human groups who have visited the site.